Comparative analysis of synergistic effects of phosphorus enrichment and hydroxyapatite nucleation on anammox granular sludge - Yanjun Zhu; Dong Li; Huiping Zeng; Sibo Fu; Yuliang Zhu; Jifang Zheng; Sen Yang; Songyue Li; Jie Zhang (Water Research X)
Combined nutrient removal and phosphorus recovery are pivotal for advancing sustainable wastewater treatment technologies. Despite the proven efficacy of anammox granular sludge systems in nutrient removal, the long-term structural development, microbial dynamics, and resource recovery potential of these systems remain insufficiently understood, particularly under municipal wastewater conditions at the microscopic level. Addressing this gap is critical to optimizing reactor performance and enhancing sustainability. In this study, we investigated the impact of phosphorus enrichment on granular sludge characteristics using two reactors. The phosphorus-free reactor (R1) facilitated the rapid formation of hollow granular sludge, with particle sizes growing rapidly—yet with significant variability—and total nitrogen (TN) removal efficiencies ranging between 74.86 % and 86.24 %. In contrast, the phosphorus-enriched reactor (R2) was supplemented to promote hydroxyapatite (HAP) nucleation, resulting in slower but more organized growth of dense granules with a narrower size distribution and consistently higher nitrogen removal efficiencies (75.17 %–91.97 %). Notably, phosphorus removal efficiency in R2 peaked when granules reached approximately 800 μm, attributable to HAP-mediated adsorption and precipitation. Furthermore, the relative abundance of key anammox bacteria, such as Candidatus Brocadia, increased dramatically from 1.28 % in R1 to 18.32 % in R2, while Denitratisoma also proliferated. Despite structural differences, similar amounts of floating sludge were observed in both reactors, likely due to gas entrapment and extracellular polymeric substances (EPS) production. These findings demonstrate that phosphorus enrichment not only enhances nitrogen removal and phosphorus recovery but also modulates microbial community composition and granule morphology.